1980
DOI: 10.1080/00288330.1980.9515879
|View full text |Cite
|
Sign up to set email alerts
|

Surface distribution of albacore tuna,Thunnus alalungaBonnaterre, in relation to the Subtropical Convergence Zone east of New Zealand

Abstract: Trolling surveys showed that albacore tuna are about equally abundant in subtropical and Subtropical Convergence Zone surface waters off the south-east coast of New Zealand. Few albacore were located in Subantarctic Surface Water, indicating that the Subtropical Convergence Zone is the southern limit for albacore in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
1
4
1
Order By: Relevance
“…The salinity of the former is less than that of the latter, with range of the ALB closely correlated to catch rate is from 34.68 to 34.95 PSU, and the range more closely correlated to catch rate is from 34.72 to 34.92 PSU with the proportion of total 1,157 (90.95 %) of the total 1272 ALB caught. This result was almost similar with Roberts (1980), stated that most ALB were caught either in subtropical water or in the Subtropical Convergence Zone with range of salinities 34.6 -35.4 0 /00 in New Zealand water. Different result from Arrizabalaga et al (2015) which states that ALB and skipjack showed clearly defined preferred salinity ranges, at around 36-37 PSU.…”
Section: Discussionsupporting
confidence: 90%
“…The salinity of the former is less than that of the latter, with range of the ALB closely correlated to catch rate is from 34.68 to 34.95 PSU, and the range more closely correlated to catch rate is from 34.72 to 34.92 PSU with the proportion of total 1,157 (90.95 %) of the total 1272 ALB caught. This result was almost similar with Roberts (1980), stated that most ALB were caught either in subtropical water or in the Subtropical Convergence Zone with range of salinities 34.6 -35.4 0 /00 in New Zealand water. Different result from Arrizabalaga et al (2015) which states that ALB and skipjack showed clearly defined preferred salinity ranges, at around 36-37 PSU.…”
Section: Discussionsupporting
confidence: 90%
“…has been occupying sections off the east coast of North Island as a component of his rock-lobster research. There have been extensive temperature and salinity observations made as part of fisheries-related programmes off the north-eastern North Island (Mercer 1979;Grassland 1980;Habib et al 1980Habib et al , 1982 eastern coast of North Island (York 1969;Lesser 1978;Roberts 1980), and around the complete North Island (JAMARC Report 1981). Two major multi-disciplinary projects have been mounted, the Maui Environmental Project guided by the University of Auckland and involved primarily with western Cook Strait, the site of the Maui Field, and the West Coast Project guided by the NZOI and involved primarily with the western coast of South Island.…”
Section: Continental Shelfmentioning
confidence: 97%
“…Often an increase in biological activity along such fronts is called the "edge-effect" and most fish have been found to accumulate at fronts (Roberts, 1980;Kleckner and McCleave, 1988;Castillo et al, 1996;Reese et al, 2011). Fish accumulations along fronts are driven by two factors, optimum temperature conditions and increased prey availability at the front (Owen, 1981;Largier, 1993).…”
Section: Importance Of Cooling Eventsmentioning
confidence: 99%